An open-label randomised controlled trial evaluating the efficacy of a meningococcal serogroup B (4CMenB) vaccine on Neisseria gonorrhoeae infection in gay and bisexual men: the MenGO study protocol - Caroline Thng; Evgeny A. Semchenko; Ian Hughes; Maree O'Sullivan; Kate L. Seib (BMC, 2023)
Abstract Background Gonorrhoea is an ongoing public health concern due to its rising incidence and the emergence of antibiotic resistance. There are an estimated 82 million new Neisseria gonorrhoeae infections each year, with several populations at higher risk for gonococcal infection, including gay and bisexual men (GBM). If left untreated, infection can lead to serious morbidity including infertility, sepsis and increased risk of HIV acquisition. Development of a gonorrhoea vaccine has been challenging, however there is observational evidence that serogroup B meningococcal vaccines, used to protect against the closely related bacteria Neisseria meningitidis, could provide cross-protection against N. gonorrhoeae. Methods The MenGO (Meningococcal vaccine efficacy against Gonorrhoea) study is a phase III open-label randomised control trial in GBM to evaluate the efficacy of the four-component meningococcal serogroup B vaccine, 4CMenB, against gonorrhoea. A total of 130 GBM will be recruited at the Gold Coast Sexual Health Clinic, Australia, and randomised to either receive 2 doses of 4CMenB or no intervention. Participants will be followed up for 24 months with testing for N. gonorrhoeae and other sexually transmissible infections every three months. Demographics, sexual behaviour risk, antibiotic use, and blood samples for analysis of N. gonorrhoeae-specific immune responses, will be collected during the study. The primary outcome is the number of N. gonorrhoeae infections in participants over 2 years measured by nucleic acid amplification test (NAAT). Secondary outcomes are vaccine-induced N. gonorrhoeae-specific immune responses, and adverse events in trial participants. Discussion This trial will determine if the 4CMenB vaccine is able to reduce N. gonorrhoeae infection. If shown to be effective, 4CMenB could be used in gonococcal prevention. Analysis of 4CMenB-induced immune responses will increase understanding of the type of immune response needed to prevent N. gonorrhoeae, which may enable identification of a potential correlate of protection to aid future gonorrhoea vaccine development. Trial registration The trial has been registered on the Australian and New Zealand Clinical Trials Registry (ACTRN12619001478101) on 25 October 2019.